2000
DOI: 10.1164/ajrccm.162.1.9907119
|View full text |Cite
|
Sign up to set email alerts
|

Permissive Hypercapnia Impairs Pulmonary Gas Exchange in the Acute Respiratory Distress Syndrome

Abstract: Current recommendations for mechanical ventilation in the acute respiratory distress syndrome (ARDS) include the use of small tidal volumes (VT), even at the cost of respiratory acidosis. We evaluated the effects of this permissive hypercapnia on pulmonary gas exchange with the multiple inert gas elimination technique (MIGET) in eight patients with ARDS. After making baseline measurements, we induced permissive hypercapnia by reducing VT from 10 +/- 2 ml/kg to 6 +/- 1 ml/kg (mean +/- SEM) at constant positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
2
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 31 publications
3
44
2
8
Order By: Relevance
“…The study of RALPH et al [38] included data obtained during progressive application of PEEP and did not observe the development of high V′A/Q′ units at the higher levels of PEEP that had been noted in the dog model of ALI. A current era MIGET study of ARDS patients by FEIHL et al [40] comparing the gas exchange responses to ventilation with tidal volumes of 10 cm A final potential influence on the physiological VD/VT in the most severely ill ARDS patients relates to the overall V′A/Q′ ratio. For patients with a very low cardiac output who are receiving very high V′E, the overall V′A/Q′ ratio may exceed 5 L·L .…”
Section: Factors Contributing To the Elevated Vd/vt In Ardsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of RALPH et al [38] included data obtained during progressive application of PEEP and did not observe the development of high V′A/Q′ units at the higher levels of PEEP that had been noted in the dog model of ALI. A current era MIGET study of ARDS patients by FEIHL et al [40] comparing the gas exchange responses to ventilation with tidal volumes of 10 cm A final potential influence on the physiological VD/VT in the most severely ill ARDS patients relates to the overall V′A/Q′ ratio. For patients with a very low cardiac output who are receiving very high V′E, the overall V′A/Q′ ratio may exceed 5 L·L .…”
Section: Factors Contributing To the Elevated Vd/vt In Ardsmentioning
confidence: 99%
“…Hence while physiological dead space abnormalities in ARDS patients are a compelling indicator of prognosis, the interpretation that abnormal values primarily represent the creation of lung parenchyma that is ventilated but not perfused is not consistent with the human data obtained utilising MIGET. The physiological dead space abnormalities in ARDS patients supported with the currently utilised 6 cm 3 ·kg −1 tidal volumes arise primarily as a consequence of the presence of both shunt and increased low and mid-range V′A/Q′ heterogeneity [40].…”
Section: Factors Contributing To the Elevated Vd/vt In Ardsmentioning
confidence: 99%
“…The attendant increases in blood carbon dioxide tension and acidosis has been referred to as "permissive" hypercapnia, a consequence of low tidal volume ventilation that for years was largely regarded as a tolerated adverse effect. In the absence of clear supporting data, some have advocated alkali administration to counteract the perceived deleterious effects of this hypercapnic acidosis (6,25). In fact, the ARDSNet protocol provided for the use of sodium bicarbonate and cited the buffering of acidosis and partial correction of hypercapnia as potential mechanisms of survival benefit associated with the low tidal volume ventilatory strategy (25).…”
mentioning
confidence: 99%
“…Not all investigators have reported benefit from hypercapnia, which has been implicated in pulmonary (6,16,17) and extrapulmonary (21,28) organ dysfunction, findings that have likely spurred further interest in the use of buffers. Bicarbonate buffers react to liberate carbon dioxide, which, because of high membrane permeability, may raise concern for further intracellular acidosis (9), a potentially operative, although unproven, mechanism in studies demonstrating worsened lung barrier function with buffering of hypercapnic acidosis (13,18).…”
mentioning
confidence: 99%
“…27 In contrast, buffering of the hypercapnia attenuated its protection. 28 Even though, in human adults a crossover study showed that permissive hypercapnia resulted in increased pulmonary shunt, 29 data from animals with therapeutic hypercapnia show that this effect is caused by low tidal volume ventilation and not hypercapnia. 30 In very low birth weight infants, permissive hypercapnia reduced autoregulation of cerebral blood flow, 18 but randomized clinical trials have not shown an increase in intracranial hemorrhage (see later).…”
Section: Introductionmentioning
confidence: 99%